Bending analysis of sandwich plate by using WRBF. (March 2019) - Kumar, Chandan; Kumar, Arbind
Abstract: In the present paper, an accurate approach is made for the bending analysis of sandwich plate by using Wendland-C2 radial basis function(WRBF) based meshfree method. Governing differential equations(GDEs) are derived based on the Energy principle. WRBF based meshfree method is implemented for discretizing the GDEs. Convergence and validation of the developed MATLAB code is obtained. Accuracy of the present work is determined by comparing the obtained results with available published results.